An intrinsic mechanism controls reactivation of neural stem cells by spindle matrix proteins - Song Li; Chwee Tat Koe; Su Ting Tay; Angie Lay Keng Tan; Shenli Zhang; Yingjie Zhang; Patrick Tan; Wing-Kin Sung; Hongyan Wang (Nature Communications, 2017)
The spindle matrix proteins, including Chro, are known to regulate mitotic spindle assembly in the cytoplasm. Here the authors show that in Drosophila larval brain, Chro promotes neural stem cell (NSC) reactivation and prevents activated NSCs from entering quiescence, and that Chro carries out such a role by regulating the expression of key transcription factors in the nucleus.